The impact of out of pocket payments on health care inequality: the case of national health insurance in South Korea - Lee, Weon-Young; Shaw, Ian (MDPI, 2014)
The global financial crisis of 2008 has led to the reinforcement of patient cost sharing in health care policy. This study aimed to explore the impact of direct out-of pocket payments (OOPs) on health care utilization and the resulting financial burden across income groups under the South Korean National Health Insurance (NHI) program with universal population coverage. We used the fourth Korean National Health and Nutrition Examination Survey (KNHNES-IV) and the Korean Household Income and Expenditure Survey (KHIES) of 2007, 2008 and 2009. The Horizontal Inequity Index (HIwv) and the average unit OOPs were used to measure income-related inequity in the quantitative and qualitative aspects of health care utilization, respectively. For financial burden, the incidence rates of catastrophic health expenditure (CHE) were compared across income groups. For outpatient and hospital visits, there was neither pro-poor or pro-rich inequality. The average unit OOPs of the poorest quintile was approximately 75% and 60% of each counterpart in the richest quintile in the outpatient and inpatient services. For the CHE threshold of 40%, the incidence rates were 5.7%, 1.67%, 0.72%, 0.33% and 0.27% in quintiles I (the poorest quintile), II, III, IV and V, respectively. Substantial OOPs under the NHI are disadvantageous, particularly for the lowest income group in terms of health care quality and financial burden.